2022
DOI: 10.3390/app122111047
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Parameter Effects on Solidification/Melting Processes Using Twin Concentric Helical Coil: Experimental Investigations

Abstract: Moving the load peak to consume electrical power is valuable in air conditioning systems. Consequently, the current study presents an experimental thermal investigation of an ice storage system. For this purpose, a twin concentric helical coil (TCHC) is utilized. The coil is submerged in distilled water in an insulated tank. The main aim is to explore the effect of geometrical/operating conditions for the TCHC on percentage energy stored/regained, solidified/melted mass fraction, and average charging/dischargi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The findings showed that the used fins enhanced the solidification rate. Recently, Refaey et al [25] presented an experimental investigation on the geometrical effects of twin concentering helical coil on solidification/melting processes. The outcomes revealed that the discharge time improved by 79% for total energy achieved when coil pitch grows from 30 to 50 mm for tube diameter 9.52 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the used fins enhanced the solidification rate. Recently, Refaey et al [25] presented an experimental investigation on the geometrical effects of twin concentering helical coil on solidification/melting processes. The outcomes revealed that the discharge time improved by 79% for total energy achieved when coil pitch grows from 30 to 50 mm for tube diameter 9.52 mm.…”
Section: Introductionmentioning
confidence: 99%